DIVERSITY, DISTRIBUTION AND BIOLOGICAL ACTIVITY OF SOFT CORALS (OCTOCORALLIA, ALCYONACEA) IN SINGAPORE - Beverly Pi Lee Goh; Grace Enhui Tan; Lik Tong Tan (JOURNAL OF COASTAL DEVELOPMENT, 2009)
The Southern Islands of Singapore are known to contain coral reefs which are high in biodiversity. However, the diversity of soft corals had received little attention to date. This study was conducted to determine the soft coral diversity in Singapore reefs as well as to conduct preliminary bioactivity tests on the organic extracts from these soft corals. A 100-meter line transect was used to survey soft corals at a 3m depth at ten different sample sites. Sclerites from samples were used to identify the soft corals to the generic level. This study uncovered the following genera of soft corals: Carijoa spp., Cladiella spp., Sinularia spp., Lobophytum spp., Sarcophyton spp., Stereonephthya spp., and Nephthea spp. In addition, an unidentified genus of soft coral was observed at Kusu Island. Cladiella spp. yielded the highest number of colonies, and Sarcophyton spp. had the highest coverage in terms of total colony diameter. The brine shrimp (Artemia salina) toxicity assay was carried out to screen for toxicity of the soft coral extracts at concentrations of 10, 100, and 1000 ppm. Results showed high levels of toxicity in extracts of Sarcophyton spp. and Cladiella spp., indicating that these soft corals are potentially good sources of bioactive compounds for drug discovery.